2011
DOI: 10.1155/2011/616725
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis Following Azacitidine Therapy

Abstract: The present report describes the first recognized case of cytomegalovirus (CMV) colitis following azacitidine therapy. A 66-year-old woman with myelodysplastic syndrome developed CMV colitis, which responded to treatment with ganciclovir. Currently, patients receiving azacitidine do not undergo CMV testing, or receive prophylaxis or CMV-free blood products; however, this policy needs to be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…There is increasing incidence of CMV reactivation in patients undergoing conventional chemotherapy. In our literature review, the earliest reported case of CMV colitis after standard chemotherapy was in a patient receiving azacitidine, published in 2011 [ 2 ]. A recent study involving 15 cancer patients with 11 head and neck cancers, two lung cancers, one lymphoma, and one rectal cancer showed that all but one patient experienced CMV reactivation during the course of chemotherapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing incidence of CMV reactivation in patients undergoing conventional chemotherapy. In our literature review, the earliest reported case of CMV colitis after standard chemotherapy was in a patient receiving azacitidine, published in 2011 [ 2 ]. A recent study involving 15 cancer patients with 11 head and neck cancers, two lung cancers, one lymphoma, and one rectal cancer showed that all but one patient experienced CMV reactivation during the course of chemotherapy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A conforto del ruolo eziologico svolto dal CMV nell'esacerbazione della malattia, dati di letteratura riportano remissione della fase di riacutizzazione e riduzione della morbilità dopo trattamento dell'infezione con terapia antivirale (Ganciclovir o Foscarnet) (4,8). Analogamente, il nostro paziente, trattato con Ganciclovir per 15 gg., presentava, al termine della terapia, assenza di viremia su sangue e remissione della sintomatologia clinica (dolore addominale e rettorragia).…”
Section: Conclusioniunclassified
“…Here, we present a case of CMV colitis following treatment with azacitidine and venetoclax for acute myeloid leukaemia (AML). While reviewing the literature, we found only one prior case report mentioning the occurrence of CMV colitis following azacitidine single-agent administration [ 4 ]. However, it is important to highlight that CMV reactivation/disease is most likely an under-diagnosed condition in AML settings before HSCT, as previously reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%